A conservative and fertility preserving treatment for interstitial ectopic pregnancy. (12th April 2013) - Wright, Sarah D.; Busbridge, Romy C.; Gard, Gregory B.
<x xml:space="preserve">Abstract</x> This is a case series of women presenting to a tertiary care centre with a diagnosis of interstitial pregnancy. Dilatation and evacuation was performed under ultrasound control with systemic methotrexate post‐operatively. All women had successful termination of their interstitial pregnancy. Although described in the international literature, this is the first time that this technique has been documented in Australia, and it may ultimately prove to be a relatively safe and simple fertility preserving method of treating women with unruptured interstitial pregnancies.